2022
DOI: 10.12973/eu-jer.11.3.1555
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Multimedia Learning for Distance Education Toward Early Childhood Critical Thinking During the COVID-19 Pandemic

Abstract: <p style="text-align: justify;">The government has imposed social restrictions during the COVID-19 pandemic, affecting the education sector, including the early childhood school. Distance education offers different methods from the conventional methods, as the students are expected to gain the same skills, including critical thinking skills. Therefore, teachers must provide distance learning innovations using relevant learning media, such as multimedia-based learning. This research aims to assess the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Activities at Mekar Sari KB still used worksheets, even though learning using the play method encourages activity, knowledge, and social interaction of children (Dhieni et al, 2022) in (Damrongpanit, 2022). After giving the order, the teacher observed the children (Visual Looking On), where the teacher only saw the children doing activities.…”
Section: Resultsmentioning
confidence: 99%
“…Activities at Mekar Sari KB still used worksheets, even though learning using the play method encourages activity, knowledge, and social interaction of children (Dhieni et al, 2022) in (Damrongpanit, 2022). After giving the order, the teacher observed the children (Visual Looking On), where the teacher only saw the children doing activities.…”
Section: Resultsmentioning
confidence: 99%
“…According to Kuloğlu (2022) pertaining to 21st-century skills, (Fletcher & Dumford, 2021) teachers have a responsibility to guide and encourage production readiness, curiosity, problem-solving skills, and critical thinking in their students. Thorndahl & Stentoft (2020) emphasized that nowadays critical thinking is at the top of the agenda (Fikriyatii et al, 2022;Maison et al, 2022) and very important and increasingly needed (Ristanto et al, 2022;Suparman, 2022). Facione (2011) confirms that critical thinking skill of our thinking is vital to our quality of life.…”
Section: Introductionmentioning
confidence: 89%
“…Akinbadewa (2020) suggested that the multimedia teaching approach can help to improve the performance of students in biology in secondary schools from its current status. Multimedia resources are viewed as a crucial part of our teaching strategies and assist in the development of knowledge of successful teaching techniques in a student-centered setting (Choiriyah et al, 2022). Students can learn more effectively from welldesigned multimedia resources that combine words and images than they can from more conventional forms of instruction that rely just on words (Choiriyah et al, 2022;Plowman & Stephen, 2005).…”
Section: Statement Of the Research Problemmentioning
confidence: 99%
“…Multimedia resources are viewed as a crucial part of our teaching strategies and assist in the development of knowledge of successful teaching techniques in a student-centered setting (Choiriyah et al, 2022). Students can learn more effectively from welldesigned multimedia resources that combine words and images than they can from more conventional forms of instruction that rely just on words (Choiriyah et al, 2022;Plowman & Stephen, 2005). Therefore, in light of the foregoing, this study was carried out to determine the impact of multimedia instruction on students' academic performance in biology at CDSS in Dedza, Malawi.…”
Section: Statement Of the Research Problemmentioning
confidence: 99%